From ELT to CLIL: Preparing Language Teachers for Content-Driven Instruction - Morteza Amirsheibani; Dastonjon Uktam o'g'li2 Rustamov (International Journal Of Humanities Education and Social Sciences (IJHESS), 2026)
CLIL is now used in many educational settings, yet the role of the language teacher within CLIL is still not always clear, especially for those who were trained primarily as ELT practitioners. In many EFL contexts, language teachers are suddenly expected to work with subject content, support content lessons, or cooperate with subject teachers, often without much preparation for this shift. From experience in classrooms and teacher training, this transition is rarely smooth. Teachers frequently express concerns about their level of subject knowledge, about losing focus on language, or about not knowing how far their familiar ELT techniques can be adapted for content-based work. These concerns tend to surface repeatedly in training sessions and reflective discussions. This article looks at these practical issues rather than at CLIL theory alone and argues that the problem is not a lack of content expertise. Instead, the main challenge lies in how teachers understand their role in content-driven instruction. The article suggests that language teachers contribute most effectively to CLIL when they focus on mediating meaning through language, interaction, and task design. It outlines practical directions for teacher preparation that build on existing ELT skills and experience, rather than expecting language teachers to become subject specialists